Tear Completion Versus In Situ Repair for 50% Partial-Thickness Bursal-Side Rotator Cuff Tears: A Biomechanical and Histological Study in an Animal Model - Pulatkan, Anil; Anwar, Wasim; Ayik, Omer; Bozdag, Ergun; Yildirim, Ayse Nur; KAPICIOĞLU, Mehmet; KAPICIOĞLU, MEHMET; TUNCAY, İBRAHİM; TUNCAY, İBRAHİM; Bilsel, Kerem; BİLSEL, İSMAIL KEREM (My University, 2020)
Background: